Changing the Composition of Beginning Teachers: The Role of State Alternative Certification Policies. Issue 7 (November 2022) - Redding, Christopher
Drawing on nationally representative data from six cohorts of beginning teachers from the Schools and Staffing Survey and the National Teacher and Principal Survey, this study applies a difference-in-differences research design to examine the relationship between changes to state-level alternative certification policies and the characteristics of new teachers. The introduction of alternate routes into teaching is associated with an increase in the fraction of new teachers of color in a state and the new teachers who graduated from selective colleges. No evidence was found of a relationship with the relative share of male teachers or teachers of in-demand subjects.